Non-Violence - Moussa, Mohammed; Moussa, Mohamed Mahmoud Mokhtar Habıb (Hurst & Company, 2018)
Since the 1960s, the Syrian scholar Shaykh Jawdat Said, a dissenting figure in the Arab world, has been promoting the value of non-violence. He has consistently argued against linking violence, particularly religious violence, with sacred texts. Islam, according to Said, is pre-eminently a pacifist religion in the broadest sense of inner convictions (values) shaping external behaviour (politics). Although the omnipotence of God is duly acknowledged by Said, the role of humanity in history in his writings strongly demonstrates a belief in its causal agency in the world. For Said, the Qur’an instructs Muslims to pursue two readings of the Sacred text which bring together God’s power and the free will of human beings in the same space. At times, a consequentialist ethics appears to emerge from Said’s writings that is balanced by his unconditional commitment to pacifism. Archetypal pacifists such as Prophets Abraham and Shuaib are proof of the desire of humanity to pursue rushd (truth) as opposed to ghay (error). Freedom of religion, as expressed in the Qur’anic verse ‘Let there be no compulsion in religion’ (2:256) is equated with truth. Qur’anic symbolism, what the religious historian Mircea Eliade has described as the ‘cosmogonic myths’, is reinterpreted by Said to support his unwavering commitment to non-violence, a religiously-inspired pacifism. As a result, the primordial and the modern meet in Said’s writing to raise the value of peace in the challenge of non-violence. Twentieth century writers, intellectuals and ideologues in the Arab world were obliged to traverse the nationalist promises of freedom and independence from colonialism. A linear sequence from peaceful or violent struggle to an eventual post-colonial reality prepared the rebirth of a nation. However, alternatives to nationalism evaded the totalising effects of one-party rule. Indeed, the works of Shaykh Jawdat Said from the waning of Nasserism in the 1960s to the seeming unravelling of a post-Ottoman political order in the present offer not only a dissenting reading of the Islamic sacred texts but also the past and present of the Arab world. In his works, Said’s voice rings loudly to the unorthodox, perhaps even heterodox, margins of the Islamic tradition. The moral rejection of force couched in religious terms was going against the grain in a period of populist nationalism of Gamal Abdel Nasser and Ba’athism and the resurgent alternative of Islamism. Nonetheless, the intellectual trajectory of this Dostoevsky-like figure, who continues to eke a living from the land, can be traced back to the influence of the Algerian modernist Malik Bennabi. While for Bennabi, the decline of Muslims is precisely caused by the internal factor of colonisability, self-inflicted in a very direct way, Said is similarly inclined to attribute this decline to the deep-rooted lack of freedom, at a doctrinal level, among contemporary Muslims. Freedom is linked to peace in Said’s works in sharp contrast to oppression and violence. Said has emerged as a symbol and proponent of pacifism in the Arab world.
What is Critical Muslim? Critical Muslim is a project of the Muslim Institute, London, which is a learned society of Fellows. It is published by C. Hurst and Co. (www.hurstpublishers.com), a highly respectable publisher of books on Islam and the Muslim world, as a paperback book; and co-published by Oxford University Press (Pakistan) and distributed in the United States by Oxford University Press (USA). Each issue is devoted to a single theme, which also serves as the title of the individual book.
25.1 | Values. In this issue... Merryl Wyn Davies tries to make sense of values in the post-truth age; Kabir Helminski provides a primer on Islam and human values; Boyd Tonkin welcomes strangers; Mohammad Moussa urges us to embrace pacifism; Gail Boxwell learns the meaning of ‘givenness’; Hannah McClure whirls into ecstasy; a story by the father of Catalan literature, Anselm Turmeda; and Maha Sardar’s list of ten persecuted communities.